A cross-sectional examination of wrist wrap use prevalence and characterization for ergogenic purposes in actively competing powerlifters - Harris, D.; Cardaci, T.; Cintineo, H.; Pham, R.; Dunsmore, K.; Funderburk, L.; Machek, S. (International Journal of Strength and Conditioning, 2023)
Purpose: Wrist wraps are regularly incorporated by competitive powerlifters, but several product-specific variations may influence any potential ergogenic benefits. In addition, the prevalence of athletic wrist wrap use is hitherto undescribed. Methods: Seventy actively competing powerlifters (n=70; 27±6y) who competed in the last two years were randomly recruited at sanctioned meets, whereby wrist wrap use descriptive data (wrap style [F or S], wrap length, and events used), wrap tightness (assessed via pulse oximeter-detected oxygen saturation (SpO2) and subjective discomfort [Borg CR10+]), as well as post-meet bench press one repetition maximum (1RM) were collected. Wrist wrap use prevalence data (wrap style, wrap length, and events used) were compared across TX, NC/SC, and CA regions, along with any potential correlations between both region-collapsed wrapped SpO2 and bench press. Finally, predictors of bench press 1RM (weight [kg], age [y], stiff wrap, wrap length, wrapped discomfort [WCR10+], and WSpO2) were assessed using linear regression, whereby all aforementioned statistical analyses were set at a significance level of p<.05. Results: Analyses failed to detect any significant regional differences in wrap style, length, or events used (p>0.05). Moreover, linear regression analysis revealed a significant effect (r2= 0.851, p = 0.02) where weight solely predicted bench press 1RM (p = 0.0433). Conclusions: Although we failed to detect any significant wrist wrap relationships, actively competing powerlifters nonetheless prominently utilize wraps across the regions assessed. Therefore, the potential for wrist wraps to augment bench press performance warrants further elucidation in a controlled, standardized investigation.